KOMUNIKASI ANTARPRIBADI DALAM MEMBANGUN KEPRIBADIAN SANTRI - Mudzammil Fikri Haqani; Dasrun Hidayat (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2015)
Abstract : The focus of this research is the fulfillment of emotional needs of students in the boarding school Baitul Izzah that the majority of his students are still out of educational primary school and still in dire need of attention and affection from their parents and teachers. With the fulfillment of emotional needs, students will reflect a healthy personality. This study used a qualitative approach, case study and critical theory paradigm. The result of this study is a model of emotional fulfillment students, which is Taking Role Model, a model of role-taking in order to grow the concept of self-confident students, Protection of Student Model, a boarding school rules in order to protect students feel comfortable living in the boarding school, Model Environment , an environment and parental involvement in the formation of personality, Model awareness, is the result of the awareness of parents of students personality, and Model of emotional needs which is fulfilling the emotional needs through parent and teacher relationships.Keywords: Personality, Taking Role Models, Protection of Student Model, Model of Emotional Needs. Abstrak : Fokus penelitian ini adalah metode pemenuhan kebutuhan emosional santri di pondok pesantren Baitul Izzah yang mayoritas santrinya masih mengeyam pendidikan SD dan masih sangat membutuhkan perhatian dan kasih sayang dari orang tua dan pengajar mereka. Dengan terpenuhinya kebutuhan emosional, akan tercermin kepribadian santri yang sehat. Penelitian ini menggunakan pendekatan kualitatif, metode studi kasus dengan paradigma teori kritis. Hasil penelitian ini adalah model pemenuhan kebutuhan emosional santri, yaitu Model Role Taking, merupakan model pengambilan peran agar tumbuh konsep diri santri yang percaya diri, Model Protection of Student, merupakan peraturan pondok pesantren dalam melindungi santri agar merasa nyaman tinggal di pondok pesantren, Model Environment, merupakan keterlibatan lingkungan dan orang tua dalam terbentuknya kepribadian, Model Awareness, merupakan hasil dari kesadaran orang tua terhadap kepribadian santri, dan Model of Emotional Needs yang merupakan pemenuhan kebutuhan emosional melalui hubungan orang tua dan pengajar.Kata kunci: Kepribadian, Model Role Taking, Model Protection of Student, Model of Emotional Needs